Investigating accidents related to errors of aeronautical decision-making in flight operations - Li, Wen-Chin; Harris, Don; Li, Lun-Wen; Hsu, Yueh-Ling; Wang, Thomas (Cranfield University, 2010)
Aeronautical decision-making (ADM) is defined by the FAA (1991) as ‘a systematic approach to the mental process used by aircraft pilots to consistently determine the best course of action in response to a given set of circumstances’. Jensen and Benel (1977) found that decision errors contributed to 35% of all nonfatal and 52% of all fatal general aviation accidents in the United States. Diehl (1991) proposed that decision errors contributed to 56% of airline accidents and 53% of military accidents. This research analyzes 51 accident reports obtained from ROC Aviation Safety Council (ASC) published between 1999 and 2008. Each accident report was independently analyzed using the Human Factors Analysis and Classification System (HFACS) framework (Weigmann and Shappell, 2003). The presence or the absence of each HFACS category was evaluated from the narrative of each accident report. Statistical relationships linking fallible decisions in upper management were found to directly affect supervisory practices, thereby creating the psychological preconditions for unsafe acts and hence indirectly impairing the performance of pilots’ decision-making. It was observed that 68% of accidents in this sample included a decision error. The results show clearly defined, statistically-described paths with pre-cursors to decision errors at both the immediately adjacent and also higher levels in the organization. This study provides an understanding, based upon empirical evidence, of how actions and decisions at higher managerial levels in the operation of commercial aircraft result in decision errors on the flight deck and subsequent accidents. To reduce the accident rate resulting from decision errors in flight operations the ‘paths to failure’ relating to these organizational and human factors issues must be addressed.
Keywords: Accident Prevention, Aeronautical Decision-making, Human Error, Human Factors Analysis and Classification System